Subjectivity and immaterialism in George Berkeley’s Philosophy - Echeverri Saldarriaga, Santiago (Estudios de Filosofía, 2003)
Quite often, Berkeley’s immaterialism has been misunderstood, in spite of the important role it has in his philosophy: Two reasons that could explain this fact are an one hand, it has been deemed that the negation of the existence of matter radically contradicts common sense: on the other hand, one could think that the thesis of immaterialism exclusively obeys to the theological motivations that drove Berkeley’s queries Contrary to this, the article proposes a strict philosophical reading of Berkeley’s negation of matter, by trying to show its supporting arguments critically. This tiral leads to an analysis of the relation Berkeley’s immaterialism establishes with its conception of subjectivity. First, the author moves away from the immaterialism the Irish philosopher stated, for the central argument that the latter uses to deny the existence of matter is based on a very questionable conception of the mind. Second, the author proposes to value Berkeley’s immaterialism as a more consistent position regarding subjectivity than the one offered by his immediate predecessors Descartes and Locke.